PERKEMBANGAN KOGNITIF DAN PSIKOMOTORIK ANAK USIA DINI TERHADAP MODEL PEMBELAJARAN KOOPERATIF TERINTEGRASI STICKY NOTE - Irawan, Ferry; de Lima, Cristiana Normalita; Hanip, Rival; Rafi’y, Muh.; Welerubun, Perpetua (Penerbit Widina, Widina Media Utama, 2022)
Early childhood who enter the golden age (golden age) should be trained to understand every basic competence in education. Cognitive skills are scientific skills that must be possessed by early childhood in order to be able to associate every concept with learning activities, and in one hand psychomotor skills are basic skills possessed by early childhood to integrate every cognition and affection that is manifested in early childhood attitudes. This research aims to determine the effect of the Cooperative learning model integrated with Sticky Note on the introduction of basic concepts. This research is classified as a quasi-experimental study using a non-equivalent pretest-posttest control group design. The population is 80 students with a total of three classes. The sample used was selected through the results of the equivalence test. The instrument using an essay test refers to the basic skill indicators. The analysis used the One Way Anacova Test and the results showed that the sticky note integrated cooperative learning model had an effect on cognitive and psychomotor development in early childhood.ABSTRAKAnak usia dini yang memasuki usia emas (golden age) harus dilatih untuk memahami setiap konsep dasar. Keterampilan kognitif adalah kecakapan ilmiah yang memegang peranan penting bagui anak usia dini agar mampu mengasosiasikan keterampilan dasar dengan kegiatan pembelajaran,.Tujuan penelitian untuk mengetahui pengaruh model pembelajaran Kooperatif terintegrasi stiky note terhadap pengenalan konsep dasar. Termasuk quasy experiment menggunakan Non equivalent pretest-posttest control group design. Total populasi 80 siswa dengan total tiga kelas. Sampel dalam peneltitian dipilih dengan melakukan uji kesetran pada setiap kelas. Instrumen menggunakan angket yang mengacuh pada indikator keterampilan dasar kognitif dan psikomotrik. Analisis menggunakan One Way Anacova Test dan hasilnya model pembelajaran kooperatif terintegrasi stiky note berpengaruh terhadap perkembangan kognitif dan psikomotorik pada anak usia dini secara dinamis/ berkesinambungan.